Pengenalan Kemudahan Transaksi Digital Melalui Sosialisasi Qris Kepada Warga Desa Marihat Bukit - Arini Handayani; Muhammad Alfikri; Mulia Syahputri; Nazwa Alya Alkhansa (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to introduce the convenience of digital transactions through socialization of the use of the Quick Response Code Indonesian Standard (QRIS) to residents of Marihat Bukit Village. This activity was motivated by the low public understanding of the use of non-cash transactions, particularly QRIS, which is an innovative integrated digital payment system from Bank Indonesia. Through socialization and direct practice, residents were introduced to how to use QRIS in various daily transactions, such as shopping, paying for services, and other local economic activities. The results of the activity showed an increase in public understanding and interest in the use of digital transactions that are easier, faster, and safer. It is hoped that this activity will encourage digital financial inclusion in rural areas and support government programs to expand literacy and the application of financial technology in the community. Furthermore, active community participation in this activity shows great potential to reduce dependence on cash transactions and encourage digital transformation at the village level. This activity is also expected to accelerate the transition to a more inclusive and digital-based society.